Interkonektivitas Multi Sektor dalam Upaya Pencapaian Agenda SDGs 2030 (United In Diversity) - Dharma, Dewa Putu Bhagastya; Widya Nugraha, Anak Agung Bagus Surya; Kartika Dewi, Ayu Putu Gari (Lampung Center for Global Studies (LCGS), 2024)
Sustainable Development Goals (SDGs) 2030 Agenda is a mission that countries who adopt it strive to achieve. SDGs are a blueprint oriented towards peace and prosperity for a better world, with 17 goals to be achieved. Seeing the development in every country is differ to one another, there is a need for action from various sectors to jointly achieve the SDGs. These sectors are government, private, community, non-governmental organizations or NGOs is important. This collaboration is called the multi-sector role. Each sector must carry out its respective roles simultaneously. However, even though all sectors are performing their roles to achieve the 2030 SDGs, the interconnectivity of these sectors is still a discussion. In this paper, the researcher tries to describe the relationship of the multi-sector role in an effort to achieve the 2030 SDGs agenda, especially the role of NGOs through the case study of the United In Diversity Indonesia. In addition, it tries to analyze the efforts made by these sectors towards achieving the 2030 SDGs in Indonesia. The author uses qualitative methods, and finds that the role of each sector is interconnected to one another based on their duty and qualifications in each initiative for the 2030 SDGs.